2011
DOI: 10.2466/07.11.23.28.pms.112.3.975-980
|View full text |Cite
|
Sign up to set email alerts
|

Past Speech Therapy Experiences of Individuals Exploring a New Stuttering Treatment

Abstract: Perceptions of benefits of speech therapy, success of therapy across clinical settings, reasons for returning to therapy, client-clinician relationships, and clinicians' competency were assessed in 57 participants (47 men, 10 women; M age = 34 yr.) trying a new therapy. A majority of respondents had cumulatively five or more years in therapy and at least two stuttering therapies. Respondents rated university or hospital settings as more successful than services in public schools. 70% of the respondents noted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Speech‐language pathologists (SLPs) play a unique role in implementing treatments with adults who stutter. Despite this, stuttering therapy provided by SLPs continues to be characterized negatively by adults who stutter, with high relapse rates following treatment 22,23 . Negative perceptions reported include difficulties in developing a therapeutic relationship, 24 SLPs’ reduced experience, 23 and lack of carryover of fluent speech to real‐life situations 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Speech‐language pathologists (SLPs) play a unique role in implementing treatments with adults who stutter. Despite this, stuttering therapy provided by SLPs continues to be characterized negatively by adults who stutter, with high relapse rates following treatment 22,23 . Negative perceptions reported include difficulties in developing a therapeutic relationship, 24 SLPs’ reduced experience, 23 and lack of carryover of fluent speech to real‐life situations 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Although improved mental hygiene (positive attitudes about oneself and one’s communication abilities) has been a recommended area of focus in the stuttering modification approach to treatment since the early 1900s, only more recently, in the mid-2000s, has the American Speech-Language-Hearing Association (ASHA) emphasized the need for holistic therapy, focusing on the person and their lived experiences (Bloodstein & Bernstein-Ratner, 2008). Studies showed that when fluency was the primary goal of stuttering therapy, clients had increased anxiety, depression, suicidal ideation, guilt, and shame posttherapy (Craig, Hancock, Tran, Craig, & Peters, 2002; Dayalu & Kalinowski, 2002; Guntupalli, Nanjundeswaran, Kalinowski, & Dayalu, 2011). Moreover, researchers found that clients tended to relapse nearly 96% of the time following treatment (DiLollo, Neimeyer, & Manning, 2002).…”
Section: Slp Roles In Working With Students Who Stuttermentioning
confidence: 99%